2007
DOI: 10.1111/j.1532-950x.2007.00281.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Validation of a Technique for Assessment of Canine and Feline Elbow Joint Collateral Ligament Integrity and Description of a New Method for Collateral Ligament Prosthetic Replacement

Abstract: Clinical examination findings, specifically Campbell's test, can be used to determine elbow CL integrity in dogs and cats. The contralateral elbow should be used as a control, because of interanimal variability in angles of rotation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
83
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(90 citation statements)
references
References 18 publications
5
83
0
2
Order By: Relevance
“…This degree of rotation was significantly increased when compared with normal ranges of pronation previously reported in cats, 5 and when compared with that noted preoperatively in this cat. The instability was more severe with the elbow joint held in flexion.…”
Section: Case Descriptionsupporting
confidence: 70%
See 2 more Smart Citations
“…This degree of rotation was significantly increased when compared with normal ranges of pronation previously reported in cats, 5 and when compared with that noted preoperatively in this cat. The instability was more severe with the elbow joint held in flexion.…”
Section: Case Descriptionsupporting
confidence: 70%
“…The ulnar parts of the collateral ligaments are taut throughout the range of motion, whereas the radial parts are lax in flexion, allowing an increased range of motion of the radial head. Farrell et al demonstrated the importance of the collateral ligaments for elbow joint stability in cats, 5 showing that compromise of the medial collateral ligament resulted in increased pronation, whereas compromise of the lateral collateral ligament resulted in increased supination. Luxation of the elbow joint was not possible in cats unless both collateral ligaments were impaired.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 A circumferential suture prosthesis technique was used for the surgical management of elbow luxation. 3,4 This technique consists of drilling three bone tunnels from lateral to medial across 1) the humeral epicondyles, 2) the radial head, and 3) the ulnar troachlea at the level of the ulnar trochlear notch. A single circumferential suture is passed in the humeroradial and in humeroulnar bone tunnels, respectively, as replacement for the ligaments.…”
Section: Brief Communicationmentioning
confidence: 99%
“…4 This procedure is effective in preventing elbow reluxation in vitro with excellent clinical results. 3,4 Although in the original technique nonabsorbable sutures were used, 3,4 in this case absorbable materials were employed because of the lack of long-term follow-up postoperatively due to the animal's release. The treatment performed in an acute phase and postoperatively included physical therapy under general anesthesia that contributed to the lack of articular fibrosis and the good clinical result obtained.…”
Section: Brief Communicationmentioning
confidence: 99%